Anti-glutamatergic Effects of Three Lignan Compounds: Arctigenin, Matairesinol and Trachelogenin – An ex vivo Study on Rat Brain Slices - Koech, Peter Kiplangʼat; Jócsák, Gergely; Boldizsár, Imre; Moldován, Kinga; Borbély, Sándor; Világi, Ildikó; Dobolyi, Arpád; Varró, Petra (Planta Medica, 2023)
Arctigenin is a bioactive dibenzylbutyrolactone-type lignan exhibiting various pharmacological activities. The neuroprotective effects of arctigenin were demonstrated to be mediated via inhibition of AMPA and KA type glutamate receptors in the somatosensory cortex of the rat brain. The aim of this study was to compare the effects of arctigenin with matairesinol and trachelogenin on synaptic activity in ex vivo rat brain slices. Arctigenin, matairesinol and trachelogenin were isolated from Arctium lappa, Centaurea scabiosa and Cirsium arvense, respectively, and applied on brain slices via perfusion medium at the concentration range of 0.5 – 40 µM. The effects of the lignans were examined in the CA1 hippocampus and the somatosensory cortex by recording electrically evoked field potentials. Arctigenin and trachelogenin caused a significant dose-dependent decrease in the amplitude of hippocampal population spikes (POPS) and the slope of excitatory postsynaptic potentials (EPSPs), whereas matairesinol (1 µM and 10 µM) decreased EPSP slope but had no effect on POPS amplitude. Trachelogenin effect (0.5 µM, 10 µM, 20 µM) was comparable to arctigenin (1 µM, 20 µM, 40 µM) (p > 0.05). In the neocortex, arctigenin (10 µM, 20 µM) and trachelogenin (10 µM) significantly decreased the amplitude of evoked potential early component, while matairesinol (1 µM and 10 µM) had no significant effect (p > 0.05). The results suggest that trachelogenin and arctigenin act via inhibition of AMPA and KA receptors in the brain and trachelogenin has a higher potency than arctigenin. Thus, trachelogenin and arctigenin could serve as lead compounds in the development of neuroprotective drugs.
Keywords: Arctium lappa; Centaurea scabiosa; Cirsium arvense; Asteraceae; Lignans; Hippocampus; Neocortex; Glutamate receptors; Neuronal excitability